Two Nontrivial Solutions for a Nonhomogeneous Quasilinear Elliptic System With Sign‐Changing Weight Functions - Qi, Wanting; Zhang, Xingyong (Mathematical methods in the applied sciences, 2025)
ABSTRACT We are interested in looking for two nontrivial solutions for a class of nonhomogeneous quasilinear elliptic system with sign‐changing weight functions and concave‐convex nonlinearities on the bounded domain. This kind of quasilinear elliptic system arises from nonlinear optics, whose feature is that its differential operator depends on not only ∇u$$ \nabla u $$ but also u$$ u $$. Employing the mountain pass theorem and Ekeland's variational principle as the major tools, we show that the system has at least one nontrivial solution of positive energy and one nontrivial solution of negative energy, respectively.